2020
DOI: 10.3390/su12072847
|View full text |Cite
|
Sign up to set email alerts
|

Do Local Food Products Contribute to Sustainable Economic Development?

Abstract: Local food production benefits sustainable regional development and should be considered as one the pillars of sustainable regional development strategies. Local food producers share a common heritage because of the cultural and historical ties in their regions, while consumers tend to value food products produced locally. The purpose of this article was to explore market participants’ attitudes toward the impact of local food product attributes on sustainable regional development. The authors’ findings on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 62 publications
(66 reference statements)
5
23
0
6
Order By: Relevance
“…According to different researches [47][48][49][50], external attributes are fundamental for the appreciation and purchase of wine by consumers. This is also confirmed for other typologies of local food products in other European countries [51], as Cvijanović et al [52] recently demonstrated for Serbia. In fact, it is possible to find high quality wines in many places of the world, but associating the wine with a beautiful landscape or with personal experiences, such as being hosted in the farm where a wine is produced, automatically leads to an increase in the appreciation of that wine.…”
Section: Discussionsupporting
confidence: 82%
“…According to different researches [47][48][49][50], external attributes are fundamental for the appreciation and purchase of wine by consumers. This is also confirmed for other typologies of local food products in other European countries [51], as Cvijanović et al [52] recently demonstrated for Serbia. In fact, it is possible to find high quality wines in many places of the world, but associating the wine with a beautiful landscape or with personal experiences, such as being hosted in the farm where a wine is produced, automatically leads to an increase in the appreciation of that wine.…”
Section: Discussionsupporting
confidence: 82%
“…The food market in the Republic of Serbia is dominated by locally produced foods [5][6][7][8], both organic or conventionally grown. They are positioned in the market, either as complements or substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers tend to prefer certified products, because they consider that the certificate indicates the notion of food safety [13]. They believe that local products contribute to halting biodiversity loss [5], and improving ecosystems. The consumers who are concerned about the environment consider the organic products safe from the pesticide and GMO aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Whether it is starting a new business in a community, establishing a farm, soliciting membership for a CSA, or cultivating a community garden, civic agriculture promotes the growth of social networks as people's paths cross and connect in ways they would not have before. In creating direct-to-consumer businesses for local food, farmers and entrepreneurs are dependent on a host of organizations, individuals, and government sectors to be successful (Canal Vieira et al, 2019;Christensen & Phillips, 2016;Cvijanović, Ignjatijević, Tankosić, & Cvijanović 2020;Hasanov et al, 2019;Hughes & Isengildina-Massa, 2015;Janssen, 2010). Civic agriculture addresses community issues such as rural revitalization, food availability, and social welfare, if built on a foundation of strong networks and interpersonal transaction (J.…”
Section: Cultivating Social Capitalmentioning
confidence: 99%
“…Studies over the years documenting the demographics of participants in civic agriculture reveal mixed findings. Overall, studies of CSAs (Cone & Myhre, 2000;Lass, Bevis, Hendrickson, & Ruhf 2001;Ostrom, 2008;Schnell, 2010), farmers markets (Alkon & McCullen, 2011;Byker, Shanks, Misyak, & Serrano 2012;Cvijanović et al, 2020;Wolf & Berrenson, 2003) and local food sales (Feldmann & Hamm, 2015;Godette et al, 2015;Martinez et al, 2010;O'Hara & Low, 2016;Thilmany, Bond, & Bond, 2008) show that participants tend to be white, wealthy, female, and college-educated, and are generally located in the Northeastern U.S. or West Coast near a metropolitan area. Although indicators of wealth and social class (such as proximity to a farmers market or a flexible work schedule) are often associated with greater access to local food, (Abelló, Palma, Anderson, & Waller, 2014;Galt et al, Bradley, Christensen, & Munden-Dixon, 2018;McGuirt et al, 2014;Zepeda & Nie, 2012), some scholarship posits that these demographics are not the only driver of local food consumption patterns (Guptill, Larsen, Welsh, & Kelly, 2018;Thilmany et al, 2008;Galt et al, 2017;Galt, Bradley, Christensen, & Munden-Dixon, 2019).…”
Section: Barriers To Civic Agriculturementioning
confidence: 99%